Drivers to assist technology transfer among manufacturing employees in Malaysia - Sahadevan, Mughaneswari; Jedin, Mohd. Haniff (2013)
Technology transfer is undeniable pivotal channel to upgrade development and spur growth in economies.Many drivers contributed to the performance of the transferred technology, yet few attempts were made to conduct research on a single holistic model towards the transferred technology.This study, therefore attempts to determine the relationship between absorptive capacity, transfer capacity, communication motivation and learning intent and technology transfer performance.The study used survey method. Questionnaires were used to obtain feedback from the respondents.The sample was conducted in a Japanese multinational company based in Klang Valley, Malaysia which has been established for 25 years in the making of the camera and lens. A total of 117 valid questionnaires were received. Findings showed that communication motivation is the most influential driver to assist technology transfer performance in the manufacturing firm.